Javanese Sufism: A Semiotic Analysis of Sunan Kalijaga's Suluk Linglung - Nikmaturrohmah Nikmaturrohmah; Abdul Basit (Teosofia: Indonesian Journal of Islamic Mysticism, 2024)
Classical Javanese literature covers a wide range of traditional folklore and oral traditions, including Sufism and Islamic mysticism. Among these mystical literary works is Suluk Linglung, which portrays the spiritual journey of Kanjeng Sunan Kalijaga, one of the Nine Saints (Walisongo) of Java. Written in the form of a poem, Suluk Linglung describes the spiritual journey through symbolic narratives. It explores existential confusion and stages of spiritual development, using Javanese culture and art as a vehicle for Islamic teachings that emphasize tolerance and peace. This article examines the phases of Sunan Kalijaga’s spiritual journey as described in Suluk Linglung. Applying semiotics theory to reveal the spiritual meanings of symbolic narratives, some distinct phases are identified: the encounter with Sunan Bonang, ascetic practice on the riverbank, laku ngidang (behaving like a deer), the Hajj pilgrimage to Mecca, and the meeting with Prophet Khidr. These phases represent the saint’s spiritual journey toward the True Reality. Contribution: This study contributes to the semiotics framework in interpreting Suluk Linglung, focusing on the state of being lost and confused as a spiritual-existential condition for the seeker. The phases of the spiritual journey localize the universal Sufi concepts in symbolic expressions and Javanese traditions.